A Service Quality Survey and The Anticipation Service Failure in Bonnela Shoes - Nurfitriani, Gina; Aprianingsih, Atik (The Indonesian Journal of Business Administration, 2015)
Abstract.Bonnella is one of the small and medium enterprises in fashion item, especially shoes. Bonnella provides services in the customized manufacture of shoes for men and women. Currently, Bonnella uses online sales system. Bonnella was first formed in 2010. The business went well until the end of 2013. However, since early 2014, the number of orders has dropped. A large number of complaints suspected cause of decreasing in sales. Furthermore, current Net Promoter Score (NPS) of Bonnellaâ€™s customers is -10%, a negative NPS (<0) is generally considered as bad. This situation makes the owner Bonnella worry because it could threaten Bonnella existence if left too long it will impact for the future. Bonnella wants to investigate the causal of that situation in order to maintain existence of Bonnella. Started by analyzing the external and internal environment. Internal analysis consists of current STP, marketing mix 7P, Porterâ€™s value chain, and E-ServQual analysis based on customer view. External analysis consist of PESTEL analysis, Porter's five forces analysis, and competitor analysis. The result of these environment analysis is SWOT analysis of Bonnella. Then, conduct gap analysis using E-Service Quality (E-ServQual) and E-Recovery Service Quality (E-RecSevQual) adapted from Parasuraman et.al (2005) to find wheather customer satisfaction or not. To determine the priority of solve the problem conduct Importance Performance Matrix (IPM). After the service problem were identified, the proposed solution to improve service quality were based on IPM result was combine with TOWS matrix. TOWS matrix can also be used to generate a number of possible alternative strategies based on external opportunities and threats facing can be matched with internal strengths and weaknesses to result of possible strategic alternatives. The proposed solution were followed on implementation plan. To implement the proposed solution considering the most urgent issues and the resources available.Keywords : Service Failure, Importance Performance Matrix, Gap Analysis, Online shop, Customized Shoes.Â